Analysis of the Influence of Students' Perceptions of Parental Assistance on the Internalization of Students' Moral Attitudes in Class VII Islamic Education Learning at SMP Muhammadiyah 8 Cakru - Ramadhaniameliyah Safitri; Sofyan Rofi; Hairul Huda (Universitas Cokroaminoto Palopo, 2026)
This research is motivated by the phenomenon of declining discipline and social ethics among students, as well as the importance of the synergy within the